THE EFFECTIVENESS OF USING CHARADES GAME TOWARD STUDENTS’ VOCABULARY MASTERY - Aulia Hanifah Qomar; Yulita Sahara Wati (JEE (Journal of English Education), 2021)
ABSTRACT The aim of this research is to find out the effectiveness and significance different of using Charades game in students’ vocabulary mastery at SMP Muhammadiyah Ahmad Dahlan Metro. Charades game is the activity that players a word phrase and their teammates try to guess. Charade game is a kind of game in which words are represented in pantomime. This research used an experimental research. The subjects of this research are the students at SMP Muhammadiyah Ahmad Dahlan Metro academic year 2020. There are 20 students of control group and 20 students of experimental group. The research instrument used to collect the data in this research is Test and observation. From the two classes, the experimental and control group, the measurement shows that increasing line of vocabulary mastery in experimental group is higher than control group. The result of pre-test score shows that the average score of the experimental group and the control group are 61,6and 66,6. From the score of both groups, the result shows that the control group is better than experimental group. Then, the result of the posttest in experimental group is higher than control group; the average scores are 74,2for experimental group and 68,8 for control group. It can be concluded that there are effectiveness and significant different of using Charades game in students’ vocabulary mastery. Keywords: Charades, Game, Vocabulary.